One-Pot Synthesis and In Vitro Studies of Calix[4]-2-methylresorcinarene Derivatives as Antimalarial Agents Against Plasmodium falciparum Chloroquine-Resistant Strain FCR-3 - Nursofia, Baiq Ike; Kurniawan, Yehezkiel Steven; Jumina, Jumina; Pranowo, Harno Dwi; Sholikhah, Eti Nurwening; Julianus, Jeffry; Wibowo, Susalit Setya; Fatimi, Hana Anisa; Priastomo, Yoga; Priyangga, Krisfian Tata Aneka (Indonesian Journal of Chemistry, 2024)
Malaria is an endemic disease in Indonesia caused by infection from the Plasmodium parasite. Recently, antimalarial resistance significantly contributed to the decline in the cure rate of malaria sufferers. In this work, three calix[4]resorcinarenes have been synthesized from 2-methylresorcinol and different benzaldehyde derivatives, i.e., 4-chlorobenzaldehyde, 4-methoxybenzaldehyde, and 4-dimethylaminobenzaldehyde through the one-pot synthesis procedure. The calix[4]resorcinarenes synthesis was done through a cyclo-condensation reaction by using HCl 37% as the catalyst and ethanol as the solvent in an one-pot reaction. The structures of the synthesized products were confirmed using Fourier transform infrared, proton-nuclear magnetic resonance, and liquid chromatography-mass spectrometry techniques. The antimalarial activity assay was evaluated against the Plasmodium falciparum FCR-3 strain through an in vitro study. Three synthesized compounds, i.e., C-4-chlorophenylcalix[4]-2-methylresorcinarene, C-4-methoxyphenylcalix[4]-2-methylresorcinarene and C-4-dimethylaminophenylcalix[4]-2-methylresorcinarene have been successfully synthesized in up to 97% yield. The C-4-chlorophenylcalix[4]-2-methylresorcinerene exhibited the most potent antimalarial activity with a half-maximal inhibitory concentration (IC50) value of 2.66 µM against P. falciparum FCR-3 while the C-4-methoxyphenylcalix[4]-2-methylresorcinarene and C-4-dimethylaminophenylcalix[4]-2-methylresorcinarene gave the IC50 values of 23.63 and 13.82 µM, respectively. From the results, it could be concluded that the antimalarial activity of calix[4]-2-methylresorcinarenes was influenced by the type of substituent of aromatic rings at the para position.